Sex differences in body build and their relationship to sex-specific processes of aging - Greil, Holle (Array, 1990)
Women live longer than men virtually everywhere in the world. It is not known whether the differences in male and female body size and composition contribute to this disparity in life expectancies. Data collected in a cross-sectional study of body size and other anthropometric variables in the German DemocraticRepublic document sex-specific characteristics of the growth processes underlying human sexual dimorphism. Males are larger than females at birth and remain so throughout most of their lives although female growth exceeds male during the onset of the mid-growth and adolescent growth spurts. Ultimately, males catch up and pass females in growth and attain larger size and proportions which include lower relative sitting height due to greater lower limb length. Females surpass males in the amount of total body fat early in life and are